1998
DOI: 10.1097/00007890-199811270-00022
|View full text |Cite
|
Sign up to set email alerts
|

T-Cell Receptor Variable Gene Analysis of Renal Allograft-Infiltrating Cells in Biopsy Specimens Using a Nonradioisotopic Micromethod1

Abstract: We have established a powerful method for analyzing RAIT clonality, which is especially useful for monitoring RAIT dynamics after immunosuppression therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Owens et al (25) suggested that the establishment of short-term stable renal allograft function (1 year posttransplantation) requires the deletion of certain T cells from peripheral blood. Whereas many studies described TCR usage during graft rejection in humans (14,(26)(27)(28)(29), to our knowledge, no studies on TCR usage in long-term functioning kidney transplants have hitherto been reported.…”
Section: Discussionmentioning
confidence: 98%
“…Owens et al (25) suggested that the establishment of short-term stable renal allograft function (1 year posttransplantation) requires the deletion of certain T cells from peripheral blood. Whereas many studies described TCR usage during graft rejection in humans (14,(26)(27)(28)(29), to our knowledge, no studies on TCR usage in long-term functioning kidney transplants have hitherto been reported.…”
Section: Discussionmentioning
confidence: 98%
“…Obata et al demonstrated the skew of TCR repertoires in T cells infiltrating into the renal allografts by hybridization technique (24). Hall et al demonstrated the skew of TCR repertoires in T cells infiltrating into human renal allografts by semiquantitative PCR after in vitro culture (13).…”
Section: Relationship Between Clonal T-cell Expansion and The Functiomentioning
confidence: 99%
“…Quantitative methods, including monoclonal antibodies (25), PCR (18,26), and a hybridization technique (24), have been used for the analysis of TCR repertoires. Clonality of T cells has been analyzed by Southern blot hybridization (27), CDR3 length analysis (15), and single-strand conformation polymorphism (28).…”
Section: Relationship Between Clonal T-cell Expansion and The Functiomentioning
confidence: 99%
“…The majority of studies of TcR gene usage in rejection focus on TRBV family repertoire or on alloreactive clones in vitro. (10)(11)(12)(39)(40)(41). In chronic rejection a restricted usage of TRBV has been shown by spectratyping and 'immunoscope' analysis (13).…”
Section: Discussionmentioning
confidence: 99%
“…TRBV repertoires reflect the diversity of the T-cell repertoire used by alloreactive T cells to recognize foreign tissue in transplantation. Altered TRBV repertoires have been described in studies of allograft rejection (10)(11)(12). Restricted TRBV repertoires were observed in patients with both acute and progressive chronic rejection (10).…”
Section: Introductionmentioning
confidence: 99%